1997
DOI: 10.1002/(sici)1097-0355(199723)18:3<247::aid-imhj2>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic synchrony in parent–child interactions: A link with maternal representations of attachment relationships

Abstract: The study examined the relation between maternal representations of attachment relationships from childhood and current parent–child interactions with their own preschool aged children. Thirty‐six mother–child dyads were recruited from a community sample. The Adult Attachment Interview was converted into a questionnaire (AAIQ) and used to classify mothers as either “secure” or “insecure.” The mother–child dyads then engaged in a 20‐min, videotaped play interaction task. The quality of maternal representations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 17 publications
3
34
0
1
Order By: Relevance
“…In particular, children from dyads marked by shared positive affect and conversational equality were more likely than other children to be rated by teachers as engaging in high levels of prosocial behavior with peers. Following the tenants of attachment theory, and consistent with previous research (Crandell et al, 1997;Isabella & Belsky, 1991), it may be that synchronous interaction contributes to a secure mother-child attachment relationship. In turn, securely attached children develop a working model of others as being trustworthy and are more likely to engage in prosocial behavior with peers.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In particular, children from dyads marked by shared positive affect and conversational equality were more likely than other children to be rated by teachers as engaging in high levels of prosocial behavior with peers. Following the tenants of attachment theory, and consistent with previous research (Crandell et al, 1997;Isabella & Belsky, 1991), it may be that synchronous interaction contributes to a secure mother-child attachment relationship. In turn, securely attached children develop a working model of others as being trustworthy and are more likely to engage in prosocial behavior with peers.…”
Section: Discussionsupporting
confidence: 65%
“…Consistent with this view, Gross and McCallum (2006) found that daughters who perceived their relationship with their mother as being highly synchronous had higher levels of self-esteem. Researchers also have posited that a synchronous mother-child relationship promotes cooperative views of others (Crandell, Fitzgerald, & Whipple, 1997;, enhances perspective-taking skills (Barber et al, 2001), and contributes to nonselfish choices that lead to higher levels of prosocial behavior (Kochanska et al, 2005;Raver, 1996). Indirect evidence in support of this argument comes from empirical links between synchrony and children's social competence with peers (Pettit, & Harrist, 1993), social skills (Criss et al, 2003), and positive relationships with peers (Lindsey, Mize, & Pettit, 1997).…”
mentioning
confidence: 99%
“…In a meta-analysis of 10 studies of the relation between parents' attachment representations and responsiveness, van IJzendoorn (1995) found effect sizes ranging from .35, r ϭ .17, to 1.37, r ϭ .57. Recent studies have also found parents who were classified as securely attached to be more responsive, sensitive, and warm when compared with insecure parents (Crandell, Fitzgerald, & Whipple, 1997;Pederson, Gleason, Moran, & Bento, 1998). In keeping with Belsky's (1984) model, we expected the relation between parents' attachment security and parenting to be mediated by parental personality in the form of ego-resiliency.…”
Section: Parental Characteristicsmentioning
confidence: 79%
“…The adult caregiving system is comprised of motivational strategies of infant care that are guided by internalized representations of the self as caregiver and of the infant (Solomon & George, 1996;Zeanah & Benoit, 1995). These strategies are themselves guided by the mother's own history of attachment and early caregiver interactions (Crandell, Fitzgerald, & Whipple, 1997;Slade & Cohen, 1996;Winnicott, 1960), such that the mother enacts internalized representations of self-other interactions, and this enactment in parenting behaviors shapes the development of the infant's internalized representations and attachment style (Zeanah, Benoit, Hirshberg, Barton, & Regan, 1994). Given that attachment insecurity is associated with involvement in violent intimate relationships in adulthood (Allison et al, 2008;Babcock et al, 2000), the disruptive effects of IPV on maternal caregiving representations and concomitant distortions in the infant's working attachment models may serve as a mechanism through which experiences of intimate partner violence are transmitted across generations.…”
Section: The Intergenerational Transmission Of Intimate Partner Violencementioning
confidence: 99%